PENGARUH PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA DAN KOMPETENSI TERHADAP KINERJA DOSEN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABLE MEDIASI - Syamsul Arifin; Ernani Hadiyati; Fx. Bhakti Hendra Kusuma (Bajang Institute, 2025)
This study aims to determine and analyze the effect human resources management practices and competence on lecturer performance with organizational commitment as a mediating variable. This research is categorized as an explanatory research with quantitative methods which is defined as a method based on the positivism philosophy. The sample of data in this study was calculated by using the Slovin formula, with 219 out of 485 lecturer of Civil Servants at Malang State Polytechnic (Polinema). Simple random sampling was used as a sampling technique. Then, data were anaysed by using Partial Least Square (PLS) with the Linkert scale as a measuring tool and SmartPLS 3.0 as a test tool. The results showed: (i) Human resources management has a significant effect on lecturer performance; (ii) Competence have a significant effect on lecturer performance; (iii) Human resources management has a significant effect on organizational commitment (iv) Competence have a significant effect on organizational commitment; (v) Organizational commitment has a significant effect on lecturer performance; (vi) Human resources management has a significant effect on lecturer performance through organizational commitment; (vii) Competence have a significant effect on lecturer performance through organizational commitment.